Aging Welfare and Social Policy China and the Nordic Countries in Comparative Perspective - Jing, Tian-kui.; Kuhnle, Stein; Pan, Yi.; Chen, Sheying; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This perceptive volume presents conceptual, theoretical, and empirical approaches to social policy analysis comparing China and Nordic countries in their treatment of the elderly. An international panel of experts offers valuable policy insights into issues of housing, community care, family care, pensions and social security, and mental health as China translates and adapts Western examples, particularly those set by Norway, Sweden, and Finland. The book contrasts shared issues in the contexts of economic history, accountability and service improvements, and sustainability while also examining specifically Chinese problems such as care gaps between urban and rural elders. Coverage also considers the centrality of aging policy in China as the nation works toward its long-term goal of eradicating poverty. Included among the topics: Building a welfare system with Chinese characteristics: from a residual type to moderate universalism. "Aging in community": historical and comparative study of aging welfare and social policy. Sweden: aging welfare and social policy in the 21st century. Policy responses to aging: care services for the elderly in Norway. China's elderly care policy and its future trends. Aging Welfare and Social Policy will interest professionals and researchers addressing questions of Chinese and comparative social policy, health psychologists, and sociologists focused on family, youth, and aging. .
Chapter 1: Welfare States with Nordic Characteristics -- Chapter 2: Building a Welfare System with Chinese Characteristics: From a Residual Type to Moderate Universalism -- Chapter 3: Evolution and Construction of China's Social Protection System: A Discussion from the Perspective of Shared Development -- Chapter 4: "Aging in Community": Historical and Comparative Study of Aging Welfare and Social Policy -- Chapter 5: Sweden: Ageing Welfare, and Social Policy in the 21st Century -- Chapter 6: Looking for the Easy Way Out: Demographic Panic and the Twists and Turns of Long-term Care Policy in Finland -- Chapter 7: Policy Responses to Ageing: Care Services for the Elderly in Norway -- Chapter 8: Is Finland Connected for e-Health and e-Welfare? -- Chapter 9: Social Construction, System Defect and System Quality of Welfare Policy and Regulation Framework for the Elderly of China -- Chapter 10: Social Organisations and Old Age Services in Urban Communities in China: Stabilising Networks? -- Chapter 11: Social Services for the Elderly Community Based in Urban-Rural China: Investigations in Three Provinces -- Chapter 12: 13. Appendix: China's Elderly Care Policy and Its Future Trends.
Keywords: Sociology; Social groups; Clinical health psychology; Aging; Demography; Population; Sociology of Family, Youth and Aging; Health Psychology; Ageing; Population and Demography